Development of universal influenza vaccines targeting conserved viral proteins - Jazayeri, S. D. *; Poh, Chit Laa * (MDPI, 2019)
Vaccination is still the most efficient way to prevent an infection with influenza viruses. Nevertheless, existing commercial vaccines face serious limitations such as availability during epidemic outbreaks and their efficacy. Existing seasonal influenza vaccines mostly induce antibody responses to the surface proteins of influenza viruses, which frequently change due to antigenic shift and or drift, thus allowing influenza viruses to avoid neutralizing antibodies. Hence, influenza vaccines need a yearly formulation to protect against new seasonal viruses. A broadly protective or universal influenza vaccine must induce effective humoral as well as cellular immunity against conserved influenza antigens, offer good protection against influenza pandemics, be safe, and have a fast production platform. Nanotechnology has great potential to improve vaccine delivery, immunogenicity, and host immune responses. As new strains of human epidemic influenza virus strains could originate from poultry and swine viruses, development of a new universal influenza vaccine will require the immune responses to be directed against viruses from different hosts. This review discusses how the new vaccine platforms and nanoparticles can be beneficial in the development of a broadly protective, universal influenza vaccine.